Comparative Analysis Of The Influence Of Capital Structure, Company Size, And Governance On Company Bankruptcy With Profit Quality As A Moderating Variable In The Period Before The Pandemic And During The Covid-19 Pandemic - Riyadi, Yongki; Nugroho, Lucky; Putra, Yananto Mihadi; Gal, Timea; Setiawan, Audita (Baca Dulu Publisher, 2024)
This study uses earnings quality as a moderating variable to determine a comparative analysis of the effect of capital structure, firm size, and management on corporate bankruptcy. This quantitative study uses secondary data obtained and accessible through the website of the Indonesia Stock Exchange. The sample for this study consisted of 53 refined manufacturing companies. This study uses the purposive sampling method to select the desired sample. The analysis method of this study uses linear regression analysis and moderated regression analysis as analysis tools in Eviews 12. The results show that (1) Capital structure affects the company's bankruptcy in the phase 2015-2018, but not in the phase 2019-2022. (2) The size of the company does not affect the bankruptcy of the company in the phase 2015-2018, but it has an effect in the period 2019-2022 (3) The management, in this case, the ownership of the management, has an effect on the bankruptcy of the company also in 2015. -in phase 2018 and phase 2019-2022 (4) Institutional ownership affects the bankruptcy of the company and in the phases 2015-2018 and 2019-2022 (5) The quality of results does not affect the bankruptcy of the company in the 2015-2018 phase, but it has an effect in the 2019-2022 phase. (6) Earnings quality can slow company size to corporate bankruptcy in both phases, 2015-2018 and 2019-2022. (7) In the phase 2019-2022, the quality of the result can slow down the ownership.